An intravenous clarithromycin lipid emulsion with a high drug loading, H-bonding and a hydrogen-bonded ion pair complex exhibiting excellent antibacterial activity - Haoyu Gong; Sicong Geng; Qi Zheng; Puxiu Wang; Lifeng Luo; Xiuzhi Wang; Yan Zhang; Yu Zhang; Haibing He; Xing Tang (Elsevier, 2016)
The aim of this study was to develop an intravenous clarithromycin lipid emulsion (CLE) with good stability and excellent antibacterial activity. The CLE was prepared by the thin-film dispersed homogenization method. The interaction between clarithromycin (CLA) and cholesteryl hemisuccinate (CHEMS) was confirmed by DSC, FT-IR and 1H NMR analysis. The interfacial drug loading, thermal sterilization, freeze-thaw stability, and in vitro and in vivo antibacterial activity were investigated systematically. DSC, FT-IR and 1H NMR spectra showed that CHEMS (CLA: CHEMS, M ratio 1:2) could interact with CLA through H-bonding and a hydrogen-bonded ion pair. The CHEMS was found necessary to maintain the stability of CLE. Ultracentrifugation showed that almost 88% CLA could be loaded into the interfacial layer. The optimized CLE formulation could withstand autoclaving at 121 °C for 10 min and remain stable after three freeze-thaw cycles. The in vitro susceptibility test revealed that the CLA-CHEMS ion-pair and CLE have similar activity to the parent drug against many different bacterial strains. The in vivo antibacterial activity showed that the ED50 of intravenous CLE was markedly lower than that of CLA solution administrated orally. CLE exhibited pronounced antibacterial activity and might be a candidate for a new nanocarrier for CLA with potential advantages over the current commercial formulation.